Effect of temperature on the impact ignition behavior of the aluminum/polytetrafluoroethylene reactive material under multiple pulse loading. (April 2020) - Ren, Huilan; Li, Wei; Ning, Jianguo
Abstract: An impact ignition experiment was conducted using a split Hopkinson pressure bar at 22, 65, 125, and 205 °C to study the ignition behavior of an aluminum/polytetrafluoroethylene reactive material under extreme conditions such as high temperature, pressure, and strain rate. The dynamic compression behavior, micromorphology, ignition threshold, ignition delay time, and failure characteristics of the aluminum/polytetrafluoroethylene reactive material were investigated. The results indicate that the material's sensitivity continuously increases with temperature. Moreover, three cases of ignition delay times (500–700, 1000–1100, and 1600–1700 μs) correspond to the time of the second, third, and fourth stress pulses, respectively. The combined results of scanning electron microscopy and high-speed photography show that the polytetrafluoroethylene fibers are stretched out due to their thermal softening at 125 °C, which in turn prevents the reactive material from being ignited at the third pulse. At 205 °C, the fractured specimen can be bonded between the bars by the remarkable polytetrafluoroethylene fibers, enabling the reactive material to be ignited at the third and fourth stress pulses. This study deepens our understanding of the impact ignition mechanism of aluminum/polytetrafluoroethylene reactive materials. Graphical abstract: Unlabelled Image Highlights: The reactive material is thermally softened and its strength decreases as temperature increases. Polytetrafluoroethylene fibers are formed during compression at 125 and 205 °C bridging the aluminum particles and matrix. The impact ignition behavior is affected by the stretched polytetrafluoroethylene fibers at 125 and 205 °C. The minimum specific incident energy for ignition decreases about 40% when the temperature increases from 22 to 205 °C.